Two-Stage Dynamic Pricing and Advertising Strategies for Online Video Services - Zhi Li; De-qing Tan (Discrete Dynamics in Nature and Society)
As the demands for online video services increase intensively, the selection of business models has drawn the great attention of online providers. Among them, pay-per-view mode and advertising mode are two important resource modes, where the reasonable fee charge and suitable volume of ads need to be determined. This paper establishes an analytical framework studying the optimal dynamic pricing and advertising strategies for online providers; it shows how the strategies are influenced by the videos available time and the viewers’ emotional factor. We create the two-stage strategy of revenue models involving a single fee mode and a mixed fee-free mode and find out the optimal fee charge and advertising level of online video services. According to the results, the optimal video price and ads volume dynamically vary over time. The viewer’s aversion level to advertising has direct effects on both the volume of ads and the number of viewers who have selected low-quality content. The optimal volume of ads decreases with the increase of ads-aversion coefficient, while increasing as the quality of videos increases. The results also indicate that, in the long run, a pure fee mode or free mode is the optimal strategy for online providers.